2022
DOI: 10.3390/cells11203308
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of the Prognostic and Immunotherapeutic Value of MITD1

Abstract: Microtubule-interacting and trafficking domain containing 1 (MITD1) is associated with abscission during cytokinesis. However, systematic investigation into its role in cancer is lacking. Therefore, we explored the pan-cancer role of MITD1 using multiple databases. Expression and clinical survival, immunological, and enrichment analyses were performed using R packages and online tools. For breast cancer, single-cell level analysis, immunochemistry, and in vitro experiments were performed to explore the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…tumor microenvironment (TME) is constituted of diverse immune cells, interstitial cells, extracellular matrix, and tumor blood vessels, which stimulate the onset and advancement of cancer (31). The infiltrating immune cell levels in TME usually change with tumorigenesis and progression (32). Our analysis illustrated that PDAC patients having high risk scores recorded lower ImuneScores, StromalScores and ESTIMATEScores.…”
Section: A B D Cmentioning
confidence: 79%
“…tumor microenvironment (TME) is constituted of diverse immune cells, interstitial cells, extracellular matrix, and tumor blood vessels, which stimulate the onset and advancement of cancer (31). The infiltrating immune cell levels in TME usually change with tumorigenesis and progression (32). Our analysis illustrated that PDAC patients having high risk scores recorded lower ImuneScores, StromalScores and ESTIMATEScores.…”
Section: A B D Cmentioning
confidence: 79%
“…Elevated expression of Microtubule interacting and trafficking domain-containing 1 ( MITD1 ) forecasted unfavorable prognosis in patients with low-grade glioma and GBM. For the latter, MITD1 was positively correlated to homologous recombination deficiency ( Dong et al, 2022 ). The gene Eyes absent homolog 4 ( EYA4 ) plays a putative tumor-promoting role in nervous system tumors ( Chong et al, 2023 ) and was found to promote cell proliferation in GBM ( Li et al, 2018b ).…”
Section: Resultsmentioning
confidence: 99%
“…The gene has been associated by other studies with chemoresistance and might mediate carboplatin resistance [63,64]. MITD1 is the last one of the platinum-resistant group, and the high expression of this gene is associated with low PFS [65]. The protein coded by MITD1 is recruited by ESCRT-III to midbodies and participates afterward in cytokinesis abscission [66].…”
Section: Prediction Of Platinum Response Statusmentioning
confidence: 98%